2016
DOI: 10.1149/2.0281614jes
|View full text |Cite
|
Sign up to set email alerts
|

Further Modeling of Chloride Concentration and Temperature Effects on 1D Pit Growth

Abstract: The product of diffusion coefficient and saturation concentration of metal ions (D M+ · C tot ) is associated with steady state dissolution of metal in corrosion pits. In our previous paper, D M+ · C tot was modeled for one dimensional (1D) pit dissolution of super 13Cr stainless steel (S13Cr) by taking into account the common ion effect, as well as viscosity and temperature influences. However, the modeled values were only half of the experimentally-measured D M+ · C tot , implying that D M+ and/or C tot were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
4
16
0
Order By: Relevance
“…Because of the common ion effect, the solubility of the metal cation decreases significantly with an increase in chloride concentration. This inverse relationship between the saturation concentration of metal cation and the bulk concentration of sodium chloride has also been noted by several experimental [8] and numerical studies [39,43]. In Figure 5(b), we show the dependence of pH at the pit base on the temperature and bulk concentrations.…”
Section: Effect Of Temperature and Bulk Concentrationsupporting
confidence: 82%
See 2 more Smart Citations
“…Because of the common ion effect, the solubility of the metal cation decreases significantly with an increase in chloride concentration. This inverse relationship between the saturation concentration of metal cation and the bulk concentration of sodium chloride has also been noted by several experimental [8] and numerical studies [39,43]. In Figure 5(b), we show the dependence of pH at the pit base on the temperature and bulk concentrations.…”
Section: Effect Of Temperature and Bulk Concentrationsupporting
confidence: 82%
“…The metal chloride solution near the corroding surface will reach saturation when a high enough electrical potential is applied. As demonstrated by Jun et al [43], the effect of electrolyte viscosity on mass transport in such a concentrated electrolyte cannot be ignored. The effect of viscosity η and temperature T on the diffusion coefficient can be described using the Stokes-Einstein equation…”
Section: Diffusivity and Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…Nishimoto et al 35 have also reported a sharp decrease of pH and increase of [C1 − ] resulted from the generation of micro-pits inside the crevice. Jun, Frankel and Sridhar 36,37 studied the diffusioncontrolled pit growth of Super 13Cr stainless steel and modeled the diffusion coefficient and the saturation concentration of metal ions for one-dimensional pit dissolution. They reported that the pit growth was more stable in bulk solutions with higher NaCl concentration and explained how the bulk NaCl concentration can affect the diffusion coefficients of metal ions and FeCl 2 precipitation in a growing pit.…”
Section: The Cpcc Measured At Various Applied Potentialsmentioning
confidence: 99%
“…Jun et al, and Srinivasan et al have demonstrated the importance of solution viscosity on diffusivity, indicating that the diffusion coefficient would decrease with an increase in pit depth 8,19,31. Thus, it was necessary to consider a variable diffusion coefficient due to the concentration gradient inside the pit.…”
mentioning
confidence: 99%